2012
DOI: 10.5120/9729-4202
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Information Security Awareness in the Higher Education Sector

Abstract: Information security awareness is an important contributing factor for a successful information security plan and should be properly assessed in order to suggest improvements. This explorative study directly investigated and assessed the employee information security awareness levels within a South Australian Higher Education Institution for the purpose of providing much needed insight into the extent of information awareness levels in Australian organizations. Using an online questionnaire, the study revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Thus the idea to use these questions in section A is to establish the awareness of volunteer computing. It is assumed that a respondent with basic understanding of volunteer computing will be able to attempt the questionnaire with little difficulty [8]. For the second part, the questionnaire aims to evaluate the respondents' behaviour independently of their vocabulary knowledge about volunteer computing and hence scenario-type questions were used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus the idea to use these questions in section A is to establish the awareness of volunteer computing. It is assumed that a respondent with basic understanding of volunteer computing will be able to attempt the questionnaire with little difficulty [8]. For the second part, the questionnaire aims to evaluate the respondents' behaviour independently of their vocabulary knowledge about volunteer computing and hence scenario-type questions were used.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire was designed using the approach used in a paper titled "A vocabulary test to assess information security awareness" [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, many end users are still unaware of the importance of information security and the relevant organizational requirements. Chan and Mubarak [6] found that more than fifty per cent of the employees in their study were unaware of the existence of the information security policy in their organizations.…”
Section: Introductionmentioning
confidence: 92%
“…The results of the study suggested that increased awareness and training programmes have an impact on users' compliance with information security policy. Chan and Mubarak [6] concluded that a "lack of awareness and knowledge of policies may have allowed for staff to violate such policies".…”
Section: Awareness Raising and Trainingmentioning
confidence: 99%